Hemoglobin Affinity for Oxygen in the Anginal Syndrome with Normal Coronary Arteriograms - Vokonas, Pantel S. (1974)
Oxyhemoglobin dissociation (OHD) curves were performed on whole blood (WB) from 20 patients with anginal pain, normal hemodynamics, and normal coronary arteries, as demonstrated by selective coronary cinearteriography. OHD curves in 19 of 20 patients, from zero to full saturation, were nearly identical to those in normal control subjects with values for P(50) (Po(2) at 50% saturation and pH 7.4) of 26.7±1.5 (mean±SD of the mean) torr (mm Hg) and red blood cell (RBC) levels of 2,3-diphosphoglyceric acid (2, 3-DPG) of 0.72±0.10 (mean±SD of the mean) M/M hemoglobin (Hb). Normal values for nonsmoking adults were: P(50), 26.6±1.4 (mean±SD of the mean) torr: and RBC 2,3-DPG, 0.81±0.09 (mean±SD of the mean) M/M Hb. Mean levels of carbon monoxide were normal at 0.14±0.01 (mean±SEM) ml/100 ml WB in 10 patients who were nonsmokers and 0.45±0.15 (mean±SEM) ml/100 ml WB in 10 smokers. In one patient, a heavy smoker with markedly elevated blood carbon monoxide levels, an abnormal leftward shift of the OHD curve was observed. This was corrected after discontinuation of smoking. In utilizing these methods, we could not detect consistent abnormalities of Hb affinity for oxygen at rest in the patients studied, which suggests that a defect in oxygen transport at rest is an unlikely explanation for the symptoms of chest pain in patients with the anginal syndrome and normal coronary arteriograms.